Aspectos epidemiológicos, clínicos e imunológicos de cães (Canis familiaris) (Linnaeus, 1758) com infecção por Leishmania (Leishmania) chagasi (Cunha & Chagas, 1937) provenientes do município de imperatriz, região sudoeste do estado do Maranhão, Brasil. - BRAGA, Geovania Maria da Silva (2007)
In Brazil, Canine Visceral Leishmaniasis (CVL) caused by Leishmania (Leishmania) chagasi has been reported all over the country particularly in northeast region, where the poverty and social conditions exert an important influence on health and disease. However there are few reports on the prevalence of visceral leishmaniasis among domestic dog in endemic area for human disease. The goal of this research was to verify the prevalence of the CVL in Imperatriz County, Maranhão State, Brazil, and also verify the levels of IgG1 and IgG2 anti-Leishmania antibody production and evaluate the clinical signs in these dogs. A total of 420 sera samples from domiciliated dogs were collected and analyzed by enzyme linked immunosorbent assay (ELISA) to verify the prevalence and the levels of IgG1 and IgG2 anti- Leishmania antibody production. In order to evaluate the clinical signs all dogs positive for L. chagasi antibodies by ELISA test were examined. The results showed 46.66% (196/420) were positive to serological test. It have found differences statiscally (p<0.05) between the positivity and age of the dog, but it have not observed association with relation the sex of the animals. High levels of anti- Leishmania IgG2 were observed in 29.76% (125/420) and IgG1 and IgG2 levels increased significantly between oligosymptomatic and polisymptomatic animals. However IgG1 level was detectable in a few animals. Alopecia and onicogryphosis (100.00%) were the major clinical sign observed in infected dogs following by cachexia (93.13%), apathy (88.89%) and ocular lesions (77.78%). The small percentage of dogs (5,70%) naturally infected showed the IgG1 production and the clinical signs are important to confirm the diagnosis. On the other hand, sandflies were collected by CDC trap in locality several of studied county and transported to laboratory to colonization. However, it was examined in this study, on the occasion of the observation in the Lutzomyia longipalpis colony, the fungal and bacterial contamination was reported. It was observed, Staphylococcus sp., Bacillus sp., Pseudomonas sp., Proteus sp. and Aspergillus sp. on the Lutzomyia longipalpis colony. In conclusion preventive measures should be adopted to control the Canine Visceral Leishmaniasis in this area.